The educational practices of physical educators for students with special educational needs during the pandemic - Bennasar-García, Miguel Israel (2023)
Introduction: The article analyzes the situation of students with special educational needs (SEN) who have limited their physical activities (PA) due to confinement, a situation that forces teachers to design new educational practices adapted to virtuality. Objective: To analyze the educational practices of physical education (PE) for primary level students with SEN during the pandemic in the Dominican Republic. Methodology: A qualitative, exploratory, cross-sectional, qualitative approach was used by means of a survey, using non-probabilistic sampling and content analysis with semantic networks. The study consisted of 45 teachers, who provided information on their academic teacher training, student enrollment, methodologies, strategies used and resources of the teaching process. Results: The results reflect the teachers' interest in their professional activity, as opposed to the lack of support from specialists in the classroom and a low knowledge of teaching, methodologies and strategies used from virtuality for PE aimed at students with SEN. On the other hand, most teachers did not use educational facilities for physical activities, technology was used with assistance guided by family and adults at home, especially with group physical activities in family. Conclusions: Academic activities were carried out from home and have been affected by the lack of suitable conditions for an academic space and the lack of technological resources. Teacher training in the area of PE for students with SEN should be promoted.